Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\dfrac{1}{1-x}\)+\(\dfrac{1}{1+x}\)+\(\dfrac{2}{1+x^2}\)+\(\dfrac{4}{1+x^4}\)+\(\dfrac{8}{1+x^8}\)+\(\dfrac{16}{1+x^{16}}\)
=
=\(\dfrac{4}{1-x^4}\)+\(\dfrac{4}{1+x^4}\)+\(\dfrac{8}{1+x^8}\)+\(\dfrac{16}{1+x^{16}}\)
=\(\dfrac{8}{1-x^8}\)+\(\dfrac{8}{1+x^8}\)+\(\dfrac{16}{1+x^{16}}\)
=\(\dfrac{16}{1-x^{16}}\)+\(\dfrac{16}{1+x^{16}}\)
=\(\dfrac{32}{1-x^{32}}\)
a: \(=4x^4y+6x^2y^2z-2x^5y\)
b: \(=\dfrac{24x^5}{6x^2}-\dfrac{12x^4}{6x^2}+\dfrac{6x^2}{6x^2}=4x^3-2x^2+1\)
c: \(=\dfrac{\left(2x-1\right)^2}{2x-1}=2x-1\)
d: \(=\dfrac{\left(x+5\right)\left(x^2-1\right)}{x+5}=x^2-1\)
1.\(2x\left(x-3\right)-5\left(3-x\right)=0\)
\(\Leftrightarrow2x\left(x-3\right)+5\left(x-3\right)=0\)
\(\Leftrightarrow\left(2x+5\right)\left(x-3\right)=0\)
\(\Rightarrow\left\{{}\begin{matrix}2x+5=0\\x-3=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=-\dfrac{5}{2}\\x=3\end{matrix}\right.\)
2.\(B=x^2+4x+5\)
\(B=x^2+4x+4+1\)
\(B=\left(x+2\right)^2+1\)
Vì \(\left(x+2\right)^2\ge0\forall x\)
\(\Rightarrow\left(x+2\right)^2+1\ge1\)
\(\Rightarrow Min_B=1\) khi x+2=0\(\Rightarrow\)x=-2
bài 6:
\(=\dfrac{2x^3+x^2-6x^2-3x+2x+1}{2x+1}=x^2-3x+1\)
\(x^2+y^2+z^2-2x+4y-6z=15\)
\(\Leftrightarrow\left(x-1\right)^2+\left(y+2\right)^2+\left(z-3\right)^2=29\)
Đặt \(P=\left|2x-3y+4z-20\right|=\left|2\left(x-1\right)-3\left(y+2\right)+4\left(z-3\right)\right|\)
\(P^2=\left[2\left(x-1\right)-3\left(y+2\right)+4\left(z-3\right)\right]^2\)
\(P^2\le\left(2^2+3^2+4^2\right)\left[\left(x-1\right)^2+\left(y+2\right)^2+\left(z-3\right)^2\right]=29^2\)
\(\Rightarrow P\le29\)
Dấu "=" xảy ra khi \(\left\{{}\begin{matrix}\left(x-1\right)^2+\left(y+2\right)^2+\left(z-3\right)^2=29\\\frac{x-1}{2}=\frac{y+2}{-3}=\frac{z-3}{4}\end{matrix}\right.\)
bài 1:
a. \((x+1)(x+3) - x(x+2)=7 \)
\(x^2+ 3x +x +3 - x^2 -2x =7\)
\(x^2+4x+3-x^2-2x=7\)
\(=> 2x+3=7\)
\(2x=4\)
\(x = 2\)
Bài 2:
a)
\((3x-5)(2x+11) -(2x+3)(3x+7) \)
\(= 6x^2 +33x-10x-55-6x^2-14x-9x-10\)
\(= (6x^2-6x^2)+(33x-10x-14x-9x)-(55+10)\)
\(=-65\)
\(\)
\(\dfrac{x^4+3x^3-17x^2+ax+b}{x^2+5x-3}\)
\(=\dfrac{x^4+5x^3-3x^2-2x^3-10x^2+6x-4x^2-20x+12+\left(a+14\right)x+b-12}{x^2+5x-3}\)
\(=x^2-2x-4+\dfrac{\left(a+14\right)x+b-12}{x^2+5x-3}\)
Để đây là phép chia hết cho a+14=0 và b-12=0
=>a=-14 và b=12
=>a+b=-2
(2x - 3)(x - 3)(x + 3)
=(2x-3)(x2-9)
= 2x3-18x-3x2+27
=2x3-3x2-18x+27
(2x-3)(x-3)(x+3)
=(2x-3)(x\(^2\)-9)
=2x\(^{^{ }3}\)-3x\(^2\)-18x+27